2020
DOI: 10.1038/s41467-020-15311-y
|View full text |Cite
|
Sign up to set email alerts
|

Housing temperature influences exercise training adaptations in mice

Abstract: Exercise training is a powerful means to combat metabolic diseases. Mice are extensively used to investigate the benefits of exercise, but mild cold stress induced by ambient housing temperatures may confound translation to humans. Thermoneutral housing is a strategy to make mice more metabolically similar to humans but its effects on exercise adaptations are unknown. Here we show that thermoneutral housing blunts exercise-induced improvements in insulin action in muscle and adipose tissue and reduces the effe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 85 publications
2
62
1
1
Order By: Relevance
“…In line with recent data obtained in mice at thermoneutrality (Raun et al, ), we found that exercise alone did not cause a significant response of the rat microbiome at thermoneutrality. Regarding the food withdrawal‐related compositional changes in the stool microbiome, at the genus level, most upregulated are Peptoclostridium, associated with ketone body synthesis and degradation, and Parabacteroides, associated with anti‐inflammatory effects.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In line with recent data obtained in mice at thermoneutrality (Raun et al, ), we found that exercise alone did not cause a significant response of the rat microbiome at thermoneutrality. Regarding the food withdrawal‐related compositional changes in the stool microbiome, at the genus level, most upregulated are Peptoclostridium, associated with ketone body synthesis and degradation, and Parabacteroides, associated with anti‐inflammatory effects.…”
Section: Discussionsupporting
confidence: 93%
“…However, up to now, studies on metabolic effects of fasting/food withdrawal and exercise in rodents, either including single exercise bouts (Zheng et al, ) or long‐term protocols based on caloric restriction/intermittent fasting and exercise (Marosi et al, ), are performed at temperatures inducing cold‐stress (20°C–22°C). Importantly, recent studies on mice showed that several metabolic effects of exercise are altered when animals are housed at thermoneutrality compared to room temperature (22°C), including markers of mitochondrial biogenesis and adipose browning (Aldiss et al, ; McKie et al, ), insulin sensitivity, and microbiome adaptation (Raun et al, ). The metabolic responses to food withdrawal at thermoneutrality were previously studied by our group in rats, both at 48 hr by transcriptional profiling (De lange et al, ), and over a period spanning 0 to 48 hr, with the responses resulting to be rapid and at times transient (De Lange et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…We believe so, but to detect clear effects of different compounds, we need to compare differences between the room temperature and cold challenge, since many adaptive mechanisms should exist, as thermoneutrality is vital for survival. Performing exams in only one of these conditions could lead to misinterpretations of the role of BAT and possible recruiters on thermogenesis and there is clear evidence that small differences in laboratory temperatures could lead to very different results in different animal models [ 24 , 25 , 27 29 ]. For example, if the tests were performed only after the cold challenge, we could conclude that no differences were seen between the groups, despite large differences in UCP-1mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…This study has a potential limitation: Recent work (McKie et al, 2019;Raun et al, 2020) has demonstrated that housing mice at subthermal neutral conditions, that is, room temperature, rather than at thermal neutrality can stimulate increases in mitochondrial and thermogenic proteins in adipose tissues with endurance exercise training. Housing temperature (22-24°C) may have impacted our data because the thermoneutral zone of Wistar rats is in the range of 29.5-30.5°C (Romanovsky, Ivanov, & Shimansky, 2002).…”
Section: Discussionmentioning
confidence: 99%